PEMBERIAN AIR GULA PADA BROILER PASCA MENETAS YANG DIPELIHARA SELAMA 4 MINGGU: BROWN SUGAR WATER TO POST-HATCH BROILERS RAISED UNTIL FOUR WEEKS OF AGE - Indarsih, Budi; Tamzil, MH; Haryani, NDK; Reformasi, E (Universitas Djuanda, 2023)
This study was conducted to determine the performance of 4-week-old broilers which were offered brown sugar in drinking water post hatching at a concentration of 0% as a control, 5%, 10% and 15%. The work was carried out in Moncongloe Village, Moncongloe, Maros, South Sulawesi. A total of 180 one-day old broilers of the Cobb 500 strain were divided into 4 treatments and three replications with a number of 15 chicks per cage unit measuring 25 cm2/bird and reared for up to 4 weeks of age. A complete feed produced by PT. Perkasa Feed was provided during the study. Brown sugar water was delivered adlibitum for 6 days after which the broiler chicks were placed in the cage for 12 hours. The experiment was based on a Completely Randomized Design. The study showed that providing brown sugar water with different concentrations had no effect (p>0.05) on feed intake, body weight, feed conversion ratio and mortality.